Metabolic Regulation and Behavior: How Hunger Produces Arousal - An Insect Study - Wicher, Dieter (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2007)
The metabolic state affects the level of general activity of an organism. Satiety is related to relaxation while hunger is coupled to elevated activity which supports the chance to balance the energy deficiency. The unrestricted food availability in modern industrial nations along with no required locomotor activity are risk factors to develop disorders such as obesity. One of the strategies to find new targets for future treatment of metabolic disorders in men is to gain detailed knowledge of molecular and cellular mechanisms involved in the regulation of metabolic homeostasis in less complex, i.e. invertebrate systems. This review reports recent molecular studies in insects about how hunger signals may be linked to global activation. Adipokinetic peptide hormones (AKHs) are the insect counterpart to the mammalian glucagon. They are released upon lack of energy and mobilize internal fuel reserves. In addition, AKHs stimulate the locomotor activity which involves their activity within the central nervous system. In the cockroach Periplaneta americana various neurons express the AKH receptor. Some of these, the dorsal unpaired median (DUM) neurons belonging to a general arousal system, release the biogenic amine octopamine, the insect counterpart to mammalian adrenergic hormones. The two Periplaneta AKHs activate Gs proteins, and AKH I also potently activates Gq proteins. AKH I and - less effectively - AKH II accelerate spiking of DUM neurons via an increase of a pacemaking Ca2+ current. Systemically injected AKH I stimulates locomotion in contrast to AKH II. This behavioral difference corresponds to the different effectiveness of the AKHs on the level of G-proteins.
Keywords: dorsal unpaired median neuron